RASIONALITAS BIROKRATIS DAN ETIKA EKOLOGIS DALAM MANAJEMEN PENDIDIKAN ISLAM: STUDI DI MAN KOTAWARINGIN TIMUR - Muhamad Isa Ansyori; Desi Erawati; Masdar Hilmy (MPI STAI Sangatta Kutai Timur, 2026)
This article aims to analyze the dominance of bureaucratic rationality and examine the integration of ecological ethics in Islamic education management through a qualitative study at MAN Kotawaringin Timur. The approach employed is qualitative, utilizing a field study design that incorporates in-depth interviews, observations, and documentation of the school principal, teachers, educational staff, and students. Data analysis was conducted interactively through data reduction, presentation, and drawing of conclusions. The results of the study indicate that educational management practices remain dominated by bureaucratic rationality, which is oriented toward administrative compliance, performance indicators, and formal procedures. Decision-making patterns tend to be top-down and limit collegial participation. On the other hand, ecological ethical values from an Islamic perspective, such as the concepts of khalifah, amanah, and mizan, have begun to be internalized in madrasah cultural practices, yet they have not been systematically integrated into institutional policies and management. This article identifies a gap between bureaucratic rationality and ecological ethical values in Islamic education management. Therefore, this article proposes an ecological amanah-based model of Islamic education management that integrates administrative efficiency with ethical responsibility and environmental sustainability. This model is expected to serve as an alternative in developing a more reflective, participatory, and sustainability-oriented governance framework for Islamic education.